Proyecto de inversión para la creación de una empresa dedicada a la venta de suplementos nutricionales a nivel nacional (2013)
The plan is to be carried out a study on investment for the creation of a company dedicated to the marketing of nutritional supplements nationwide. To this was taken into account different management theories and concepts of management, determining the viability of the investment. The plan consists of an inductive-descriptive methodology, and thus obtain a logical sequence that links the objectives with the conclusions, which can analyze the information obtained by the different studies. As for the objectives of the project is to identify market indicators required for the sale of nutritional supplements nationwide, just as we want to determine, technical support, financial and economic studies, the social and environmental impact, organizational aspects and legal, necessary for the creation of the company "MIPROTEINA" and viability in assembling it. As a result of the study is expected to know the trends in the market and thus the acceptance by the consumer as to the demand for nutritional supplements, as they can identify key factors for sustainable growth. Among the results also provided information about the technical and logistical aspects that are required for optimal performance of the company, and propose business strategies in order to promote and market the national nutritional supplements. This plan highlights the impact and / or contribution to society in terms of wealth of information and accessibility to products, promoting the consumption of these, and giving the necessary information about the benefits. Concluding the work demonstrates that the investment for the creation of the company MIPROTEINA SAS, is feasible, to expand into the domestic market.